Szaleństwo chrześcijaństwa: teologia i świadectwo - Dziuba, Andrzej F. (Collectanea Theologica, 2018)
In the theology of Eastern Christianity there is a special category of “God’s fools.” This is a particular image of faith and belongs to those who have had some mystical experience. The cross is marked by reason. This foolishness of the cross is the basic process in theological interpretation. The cross should shine out even more with its foolishness against the glare of evil, as it draws one to the authentic witness of faith and life. Rationality and reason are not sufficient to face evil. The large amount of help and voluminous theories on poverty do not solve the problems of the poor. The “foolishness” of the Gospel stands up against the foolishness of violence. Victory means forgiveness in God’s name, who appeared to lose the battle on the cross. The foolishness of the cross is a gift leading to life and it sparks a great light of hope which many institutions and people want to extinguish. Hope is not understood, especially when evil appears to triumph. The foolishness of love can overcome evil. “The message of the cross is folly for those who are on the way to ruin, but for those of us who are on the road to salvation it is the power of God” (1 Cor 1,18).